Minimum wages in Ireland, 1915 (1915)
1915 1914-1918 "Minimum wages in Ireland, 1915" [EP0146], 1915 The Trade Boards Act 1909 introduced minimum wages in certain industries. This letter from Marion Duggan to James Mallon, Secretary of the Central Committee for Women's Employment and of the National Anti Sweating League, complains that following the introduction of a minimum wage of 10 shillings and 10 pence per week for adult women in the confectionery trade, a Dublin employer had dismissed 150 workers with the intention of replacing them with younger women. Girls under 18 were paid 5 shillings per week. Marion Duggan was writing on behalf of the Irish Women Workers' Union, then housed in Liberty Hall, the headquarters of the Irish Transport and General Workers Union. Duggan was a law graduate (the letters following her signature are LL.B. T.C.D. - referring to Trinity College, Dublin), a socialist and pacifist, who was involved in the Irish women's suffrage movement as well as the IWWU and who made an important contribution to Irish feminists' campaigns to highlight how difficult it was to bring successful sexual abuse cases. She was also a member of the Central Committee for Women's Employment for the Provinces of Leinster, Munster and Connaught. A similar Committee was established for Ulster. The Central Committee for Women's Employment was appointed in connection with the Queen's Work for Women Fund. At this time, they had established a workshop in Liberty Hall to train women in shirt-making.